Tree planting for climate change: Coverage in the UK farming sector press. (August 2022) - Hardaker, Ashley; Bodner, Theresa; Dandy, Norman
Abstract: In recent years tree planting as a response to climate change has acquired a very high profile amongst policy-makers, scientists, the media, and the public. This 'afforestation', however, requires space: that is, land. Agriculture currently occupies very large areas of land globally meaning that it is commonly targeted as needing to make way for tree planting, and making farmers important gatekeepers to this climate change mitigation strategy. Given the importance of farming sector media outlets in reflecting, shaping and leading values and attitudes amongst the agricultural community, this paper investigates how tree planting is presented within the UK's two leading sectoral publications, Farmers Guardian and Farmers Weekly . We sample coverage at four points over a two-year period (2019–2021) which began with high-profile national media and scientific engagement with the topic. Our analysis reveals very low levels of coverage within these key publications with, on average, just 1 in 200 articles within our sample focussing on tree planting. Within this limited coverage we identify four themes which range from hostility towards the notion of trees on farms replacing agricultural practices, through to occasional recognition of the positive roles that trees on farms can play in climate change mitigation. Arguably, the lack of legitimisation within the coverage constitutes a significant barrier to woodland expansion on agricultural land. We conclude that farming media outlets could play a much stronger role in supporting the agricultural community to understand how it could contribute to climate change mitigation through bringing trees 'in' to farming systems, and to the normalisation of this within modern farming culture. Highlights: Farmers are gatekeepers to tree planting as a climate change mitigation strategy. Investigates how tree planting is presented in the UK's farming sector press. Our media analysis reveals on average, just 1 in 200 articles focus on tree planting. Themes range from hostility to trees on farms to the positive impacts they can have. Farming media could play a stronger role in bringing trees 'in' to farming systems.